LA PERSECUCIÓN SEGÚN CIPRIANO DE CARTAGO - Novás Castro, María del Mar (Antigüedad y Cristianismo, 1995)
Cipriano of Cartago was one of the most important figures in the Early Christiandom. This African Bishop mote about the most controversia1 question of the moment, especially those rellated with the discipline. The problem of the Lapsi led him to study in depth the fundamental theological debates, specially those conceming penitence, the persecutions and martyrdom, adopting a personal stand on the problems of the ecclesiastical hierarchy accepted by all the Western Christianity. (...)